Using proteomics to identify host cell interaction partners for VgrG and IglJ - Proksova, Magdalena; Rehulkova, Helena; Rehulka, Pavel; Lays, Claire; Lenco, Juraj; Stulik, Jiri (Scientific reports, 2020)
Francisella tularensis is a highly virulent intracellular bacterium and the causative agent of tularemia. The disease is characterized by the suboptimal innate immune response and consequently by the impaired adaptive immunity. The virulence of this pathogen depends on proteins encoded by a genomic island termed the Francisella Pathogenicity Island (FPI). However, the precise biological roles of most of the FPI-encoded proteins remain to be clarified. In this study, we employed stable isotope labeling by amino acids in cell culture (SILAC) in combination with affinity protein purification coupled with liquid chromatography-mass spectrometry to identify potential protein-effector binding pairs for two FPI virulence effectors IglJ and VgrG. Our results may indicate that while the IglJ protein interactions primarily affect mitochondria, the VgrG interactions affect phagosome and/or autophagosome biogenesis via targeting components of the host's exocyst complex.
Keywords: Immunity, Innate; Bacterial Proteins; hmotnostní spektrometrie; přirozená imunita; Gene Expression Regulation, Bacterial; Virulence; Mass Spectrometry; Francisella tularensis; proteomika; regulace genové exprese u bakterií; tularemie; Genomic Islands; virulence; genomové ostrovy; adaptivní imunita; Tularemia; Proteomics; Adaptive Immunity; bakteriální proteiny